Eroticism in Modern Javanese Poetry (Geguritan); an Analysis with a Semiotic Approach (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
This article intends to highlight the expressions and depictions of symbols and meanings of eroticism that are present in modern Javanese poetry texts (geguritan) as a form of Javanese literature and cultural products of society. This study seeks to reveal the symbols and meanings of eroticism that are expressed in the text of the modern Javanese poem geguritan entitled